Estimating Consumer Surplus Using Parametric and Semiparametric Truncated Recreation Demand Models: A Conceptual Note - Andrew Tan; Teofilo Ozuna, Jr. (Kajian Malaysia, 2001)
Consumers surplus is estimated from parametric and semiparametric truncated recreation demand models in a series of Monte Carlo experiments. The experimental designs simulate truncated recreational demand data under different error distributions, sample sizes, and truncation rates. Within each experiment, consumers surplus is estimatedusing obeserved and predicted demand. Summary statistic are used to determine the direction and magnitude of the error introduced into consumer surplus due to model misspecification, and to examine the robustness of consumers surplus derived from semi parametric truncated models.